Large-scale production by centrifugation of isotopically modified molybdenum for nuclear reactors and its cost evaluation. (1st December 2021) - Zeng, S.; Borisevich, V.D.; Smirnov, A.Yu.; Sulaberidze, G.A.; Zhao, K.; Jiang, D.J.
Highlights: Cost evaluation of large-scale production of isotopically modified molybdenum is performed. A simple formula is presented for cost evaluation. Cost evaluation can be carried out based on openly available data for enriched uranium production. The same methodology can be applied to evaluating production cost of other isotopically modified materials. Abstract: Molybdenum is considered as one of the substitutes for zirconium in making fuel cladding for safe reactor designs. The isotopically modified molybdenum (IMM) should be used instead of natural molybdenum to achieve higher energy efficiency, reduce uranium consumption, and mitigate the impact on the nuclear fuel cycle. This task can be fulfilled by using the same technology of gas centrifugation for uranium enrichment to remove the isotopes in natural molybdenum with larger thermal neutron absorption cross sections. Optimized double-cascade separation schemes consisting of the Q-cascade model are employed for studying massive production of IMM and evaluating the economic feasibility of production. A simple formula is derived to be able to assess the cost per kilogram of IMM, taking into account various cost-affecting factors. The results demonstrate that it is feasible to produce massively the IMM with a total thermal neutron absorption cross section equivalent to that of zirconium.